Pengaruh Sumber Informasi dan Dukungan Kelembagaan terhadap Kemandirian Petani di Provinsi Sumatera Selatan - Ali Alamsyah Kusumadinata; Sumardjo Sumardjo; Dwi Sadono; Burhanuddin Burhanuddin (Jurnal Penyuluhan, 2021)
The weak independence of farmers in managing farming is characterized by weak levels of farmer production and selling prices that are still determined by market conditions. The information sources owned by farmers are not strong enough to help farmers in analyzing problems faced by farmers ranging from land preparation, cultivation, harvesting to post-harvest. Therefore, the study aimed to look at the influence of agricultural information sources on the support of the institutional environment of farmers on the independence of farmers. This research used a quantitative approach with survey methods in Ogan Ilir Districts and Banyuasin Districts, South Sumatera Province. This study used a sample of 294 farmers who joined farmer groups. This research showed that the weak source of information used by farmers and the low support of the institutional environment results in the farmers' independence being quite weak. Farmers have not been able to build competitiveness, filter and partnership in the scope of their lives up to farmer groups. The independent model of farmers was able to explain 91% of sources of information and institutional environment support. Therefore, it was necessary to strengthen accurate, correct, in-depth information and adapt it to local site conditions.